A clinico-epidemiological study of melasma - Kumar, Akshy; Sharma, Mukul (International Journal of Research in Dermatology, 2018)
Background: Melasma is an acquired increased pigmentation of the skin, characterized by gray-brown symmetrical patches, mostly in the sun-exposed areas of the skin. Methods: The proposed study is an epidemiological cross sectional study which was carried out in the department of dermatology in a teaching institute from October 2007 to September 2008 at Pramukh Swami Medical College, Karamsad, Gujarat. A total of 60 patients were enrolled for the study over a period of one year. Results: The main age group affected was 30-39 years i.e. 48.33% patients. 50 patients were females.18 patients had a positive family history of melasma. 12 patients had a positive history of using OC Pills. Malar region was the commonest affected area found in 52 patients followed by Centro-facial in 31 and least involvement was seen in forehead region in 24 patients. 20 patients reported association of occurrence of the lesions with pregnancy, 09 patients reported sunlight to be the offending agent. Conclusions: Females were affected more commonly during their late third decade of life. Although we did not find the exact cause of melasma, we noticed that sun-exposure, pregnancy, and taking of oral contraceptive pills could precipitate or exacerbate the melasma.